Acculturation, perceived discrimination, and psychological distress: Experiences of South Asians in Hong Kong. (February 2016) - Tonsing, Kareen N.; Tse, Samson; Tonsing, Jenny C.
Although migration itself may not compromise the mental health of immigrants, the acculturative process can involve highly stressful factors that are specific to immigrant and minority status. Using structural equation modeling, this study examined the relations between acculturation orientations, perceived discrimination, acculturative stress, and psychological distress among 229 Pakistani and 218 Nepalese migrants living in Hong Kong. Although the initial hypothesized model was not confirmed, a modified model with good fit indices showed that acculturation orientation mediated the relationships of perceived discrimination and acculturative stress with psychological distress. Of all the factors in the model, acculturative stress had the strongest association with psychological distress.